The effect of functioning on Quality of Life Inventory-Disability measured quality of life is not mediated or moderated by parental psychological distress - Whitehouse, A.J.O.; Jacoby, P.; Reddihough, D.; Leonard, H.; Williams, K.; Downs, Jennepher (SPRINGER, 2021)
Purpose: The measurement of quality of life (QOL) in children with intellectual disability often relies upon proxy report via caregivers. The current study investigated whether caregiver psychological distress mediates or moderates the effects of impairment on their ratings of QOL in children with intellectual disability.